Affective Priming by Eye Gaze Stimuli: Behavioral and Electrophysiological Evidence - Chen, Tingji; Peltola, Mikko J.; Ranta, Lotta J.; Hietanen, Jari K. (Frontiers in Human Neuroscience, 2016)
The present study employed the affective priming paradigm and measurements of event-related potentials to investigate implicit affective reactions elicited by gaze stimuli. Participants categorized positive and negative words primed by direct gaze, averted gaze, and closed eyes. The behavioural response time results indicated that direct gaze implicitly elicited more positive affective reactions than did closed eyes. Analyses of the ERP responses to the target words revealed a priming effect on the N170 and an interaction on late positive potential (LPP) responses, and congruently with the behavioral results, suggested that, compared to closed eyes, direct gaze was affectively more congruent with positive words and more incongruent with negative words. The priming effect on the N170 response indicated that gaze stimuli influenced the subsequent affective word processing at an early stage of information processing. In conclusion, the present behavioral and electrophysiological evidence suggests that direct gaze automatically activates more positive affective reactions than closed eyes.